PATIENT SAFETY CULTURE IN CLINICAL CARE SETTING: A LITERATURE REVIEW - Suciati Suciati; Nurfika Asmaningrum; Suhari Suhari (UNEJ e-Proceeding, 2023)
Background: Patient safety is currently the most important global issue where many patient claims are reported for medical errors that occur in patients. Steps to overcome this with a culture of safety in health care. Methods: This research is a literature review. This study complies with PRISMA standards. Data sources for the identification of Science Direct, Pubmed, Scopus, and Google Scholar from 2013 to 2023. The keywords used include " safety culture for clinical setting"; “safety culture”; "patients safety culture". Result: The results of the study found 10 articles that met the inclusion criteria. The findings show that patient safety culture is influenced by nursing staff support care performance agreements in hospitals, career paths, work environment and perceptions of safety culture, the implementation of patient safety culture in hospitals, types of health service errors, the role of patient and hospital staff safety culture organizations. in supporting patient safety and workload. Conclusion: The conclusions obtained from the various articles in the discussion show that safety culture is very important to be implemented in health services. However, before implementing it, it is necessary to examine the factors that influence the implementation of the program so that the program can be implemented and implemented properly.